Processed bed elevation picks from airborne radar depth sounding across Ellsworth Land (2001) ... - Corr, Hugh; Smith, Andrew (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
During the 2001-02 field season a regional survey was flown on a 10 km line spacing grid over the drainage basin of the Rutford Ice stream (West Antarctica), as part of the TORUS (Targeting ice stream onset regions and under-ice systems) project. We present here the bed elevation picks from airborne radar depth sounding collected using the BAS PASIN radar depth sounding system mounted on the BAS aerogeophysical equipped Twin Otter aircraft. Data are provided as XYZ ASCII line data. ... : Radar data were collected using the PASIN radar echo sounding system (table 1 (Corr et al., 2007)). The TORUS survey involved the collection of a total of approximately 9,500 km of line data along 15 flights, with 10 km spacing. The airborne ice sounding radar system used a 4 μs linear frequency modulated pulse in addition to a standard short 2 μs pulse. Data provided here includes picks of surface and ice sheet bed elevation. Note a single flight may contain data from two or more SEGY files, identified in the SEGYname channel. Surface elevation is derived from radar altimeter for ground clearance < 750 m, and the PASIN system for higher altitudes. Channel description: Basic Channels Name Description Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_no Line Number e.g. LW200.1 Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984 Radar surfElev Surface ...